U dzerkali movy: social'ni harakterystyky nosija suržyku (na materiali sučasnoji ukrajins'koji prozy) - Fuderer, Tetyana (Array, 2014)
On the material from contemporary Ukrainian prose, the article analyzes metaphorical nominations of authorities. It was found that the semantic basis of most metaphors is the ideological opposition “own – alien”, which corresponds to the stratified notions in post-totalitarian societies. The authorities in Ukrainian linguoculture are opposed to the rest of the society, and thus their metaphorical images are dominated by negative ones.